Microtensile Repair Bond Strength of a Composite After Accelerated Artificial Aging: Effect of the Air Abrasion, Bur, Er:YAG Laser, Two-Step Self-etch Bonding, and Universal Bonding Repair System: Repaired Bond Strength of Aged Composite - Rashidi, Marie; Berangi, Simin; Chiniforush, Nasim; Ahmadi, Elham; Ranjbar Omrani, Ladan (Journal of Lasers in Medical Sciences, 2022)
Introduction: Repair of old composite restorations is a conservative approach. This study sought to compare the effects of two adhesive systems on the bond strength of repaired composites prepared by three different surface treatments: erbium-doped yttrium aluminum garnet (Er:YAG) laser irradiation, air-abrasion, and bur preparation. Methods: Eight microhybrid (Polofil Supra, VOCO, Germany) composite resin blocks were fabricated. The blocks were aged and assigned to four groups as stated by the surface treatment: (I) air-abrasion (50 μ aluminum oxide particles), (II) diamond bur (fine grit), (III) Er:YAG laser (3 W output power, 300 mJ energy) and (IV) control. After surface treatment, the blocks were acid-etched and salinized. Each group was divided two subgroups, and the Clearfil SE Bond or All-Bond Universal was applied on their surface. Composite resin was bonded to the aged composites. The blocks were cut into eight samples, and the microtensile bond strength (MTBS) was measured. Results: The maximum MTBS was noted in the air-abrasion (25.1 + 6 MPa) group, followed by the Er:YAG laser (21.2 + 4.7 MPa). The mean MTBS in laser and air-abrasion groups was significantly higher than that in other groups (P < 0.05). The mean MTBS was not significantly different between the laser and air-abrasion groups (P > 0.05). Composite resin conditioning by All-Bond Universal in laser and air-abrasion groups yielded significantly higher MTBS than the Clearfil SE Bond (P < 0.05). Conclusion: All surface treatments created acceptable bond strength. The surface treatment of the aged composite by the Er:YAG laser or air-abrasion along with the application of silane and All-Bond Universal provide high bond strength.